Disruption mitigation in tokamak reactor via reducing the seed electrons of avalanche. (15th July 2021) - Sergeev, V.Yu.; Kuteev, B.V.
Abstract: Disruption mitigation technology remains the key factor for ensuring safe and reliable operation in future large tokamaks including ITER. A novel approach analyzed in this paper aims at mitigating the runaway avalanche (RA) development by reducing the population of runaway seeds using the tungsten projectile injection into the ITER plasma just after the thermal quench. As opposed to the scenario currently discussed by the ITER team, the approach does not involve injecting a large mass of deuterium into the tokamak vacuum vessel for collisional suppression of the RA current generated. This should significantly reduce the operational problems of the ITER technological systems dealing with fueling and pumping, isotope separation, plasma heating, etc. Collecting seeds and runaways by the projectile injected might reduce the avalanche current in ITER below the level of 1 MA and its magnetic energy by more than two orders of magnitude. A tungsten rod being 8 mm inside of the square section and 80 mm in length that crosses the plasma volume with the velocity of 0.8 km s −1 radially or tangentially seems appropriate for ITER disruption conditions. Simulations of the projectile interaction with the ITER post TQ plasma revealed that its surface temperature remains below the tungsten melting point. It is also found that a railgun using the toroidal magnetic field of the tokamak is the optimal way to accelerate such a projectile.